The identification and reporting of child neglect among professionals and the general public - Bullock, Lydia (2019)
Background: Child neglect remains a challenge for professionals and the general public to identify and effectively respond to. This thesis provides a broad investigation into professionals and the public’s ability to identify and respond to child neglect. In particular exploring how different facets of child neglect impact on identification/taking action.